2021
DOI: 10.26414/a2369
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Financial Sustainability for Microfinance Institutions: Lessons for Islamic Microfinance Banks in Nigeria

Abstract: Islamic microfinance institutions play a major role in the provision of financial services to the poor and underprivileged through non-interest, equity-based products and services. To achieve these critical objectives, however, they need to be financially sustainable, which is threatened by the current economic and financial crisis caused by the Covid-19 pandemic. The objective of this paper is to review the determinants of financial sustainability of microfinance institutions with a view to drawing lessons fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…Data Collection and Processing: AI can gather and process large amounts of data from multiple sources. This data may include information from companies' mission statements, social media posts, press releases, and other public communications, Abdullahi and Othman, (2021). It can also include transactional data, user data, and feedback from users of Fintech services.…”
Section: Ai In Islamic Fintechmentioning
confidence: 99%
“…Data Collection and Processing: AI can gather and process large amounts of data from multiple sources. This data may include information from companies' mission statements, social media posts, press releases, and other public communications, Abdullahi and Othman, (2021). It can also include transactional data, user data, and feedback from users of Fintech services.…”
Section: Ai In Islamic Fintechmentioning
confidence: 99%
“…For example, although some studies have reported a positive relationship between deposits and operational self‐sufficiency (Abrar & Javaid, 2016; Aza, 2018; Bayai & Ikhide, 2018; Duguma & Han, 2018; Fadikpe et al, 2022), others have found a negative relationship (Bibi et al, 2022; Bogan, 2012; Dorfleitner et al, 2020; Gul et al, 2017). Similarly, conclusions regarding the influence of equity on financial self‐sufficiency (FSS) have also been divided, with some studies suggesting a positive impact (Abdulhakim & Mersha, 2020; Nyamsogoro, 2016; Rutanga et al, 2021; Sekabira, 2013), whereas others challenge this assertion (Ali et al, 2020; Mwizarubi et al, 2016; Perera, 2021; Quayes, 2012).…”
Section: Introductionmentioning
confidence: 99%